2012
DOI: 10.1007/s10661-012-2874-8
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network modeling of dissolved oxygen in the Heihe River, Northwestern China

Abstract: Identification and quantification of dissolved oxygen (DO) profiles of river is one of the primary concerns for water resources managers. In this research, an artificial neural network (ANN) was developed to simulate the DO concentrations in the Heihe River, Northwestern China. A three-layer back-propagation ANN was used with the Bayesian regularization training algorithm. The input variables of the neural network were pH, electrical conductivity, chloride (Cl . Cl − was found to be least effective variables o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 52 publications
2
43
0
1
Order By: Relevance
“…4 and 5 indicated that the BPNN model outperformed the MLR model in the prediction of DO content. The conclusion was consistent with that of previous research, in which the accuracy of the MLR model for predicting DO was inferior to the ANN models (Akkoyunlu et al 2011;Antanasijević et al 2013a;Wen et al 2013). The findings can be explained as follows: the correlation among water quality parameters tends to be nonlinear.…”
Section: Results Of Bpnn Modelsupporting
confidence: 92%
See 3 more Smart Citations
“…4 and 5 indicated that the BPNN model outperformed the MLR model in the prediction of DO content. The conclusion was consistent with that of previous research, in which the accuracy of the MLR model for predicting DO was inferior to the ANN models (Akkoyunlu et al 2011;Antanasijević et al 2013a;Wen et al 2013). The findings can be explained as follows: the correlation among water quality parameters tends to be nonlinear.…”
Section: Results Of Bpnn Modelsupporting
confidence: 92%
“…The appropriate neuron number in the hidden layer must be selected in advance for model construction, because too many neurons may result in overfitting problem and insufficient neurons may lead to inadequate information capture by the model (Chen and Liu 2014;Wen et al 2013). Fletcher and Goss (1993) suggested that the appropriate number of neurons in the hidden layer ranges from (a + 2n 1/2 ) to (2n + 1), where a is the output neuron number and n indicates the input neuron number.…”
Section: Results Of Bpnn Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In most research, the simply prediction of the concentration of dissolved oxygen was the aim [1,3,4,5,6,7,8,9], while in a number of studies the prediction of biological oxygen demand (BOD) was the purpose [2,7,10] and, very rarely, models were applied to the estimation of chemical oxygen demand (COD) [7,11]. MLP was applied by Rankovic et al [3] for the modelling of DO in a reservoir, in Serbia, and in their next study [8] an adaptive network-based fuzzy inference system (ANFIS) model was used on the same dataset, but with fewer input variables.…”
Section: Introductionmentioning
confidence: 99%